TRANSFORMASI MODEL PEMBELAJARAN FIQH PADA MASA PANDEMI COVID-19 DI MADRASAH ALIYAH NEGERI 2 MOJOKERTO TAHUN AJARAN 2021/2022 - Isti Muchlisianah; Khoirul Umam (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2022)
Abstract: The success of teaching and learning is something that teachers really expect in carrying out their duties. However, the teacher is not the only factor that influences the success of the study. One of the determinants of the success of teaching and learning is with the right learning model or method. The problem discussed in this study is the transformation of the fiqh learning model during the covid-19 pandemic which is a new phenomenon in the world of education. Based on the problems above, this research has 2 objectives related to the focus of the research on Transforming Fiqh Learning Models During the Covid-19 Pandemic Case Study Class XI Madrasah Aliyah Negeri 2 Mojokerto. The research objectives are 1). To Describe the Transformation of the Fiqh Learning Model During the Covid-19 Pandemic Class XI MAN 2 Mojokerto. 2). To describe the Inhibiting and Supporting Factors in the Transformation of the Fiqh Learning Model During the Covid-19 Pandemic Class XI MAN 2 Mojokerto. The data collected for observation and interviews were analyzed using data source triangulation analysis techniques. Based on the results of the study, it was found that: The fiqh learning model during the covid-19 pandemic changed into an online learning model. Online learning of fiqh is carried out with the help of several digital media such as e- learning, google meet, google classroom, whatsapp group, quizizz, camtasia studio, and renderingforest as well as the availability of madrasa digital libraries to support the implementation of online learning optimally. The teacher provides materials and assignments through the online application. Then students deposit the results of their assignments through the application as well or via e-mail. This learning model is carried out in accordance with the Circular Letter of the Four Ministers' Decree to prevent the transmission of the Covid-19 virus.